Digital transformation: banks shift to digitization and innovation (Journal of Economic Research & Business Administration, 2019)
The article discusses the digital transformations occurring in the field of finance, which are caused by many common problems and opportunities throughout the industry, whether it concerns insurance, retail, banking or other financial services. At the same time, there are several specific tasks in each of these segments of the financial industry, depending on the level of maturity of the digital transformation of the region, the overall ecosystem, the client’s context, including the use of digital channels, the scope of activities and the degree to which digitization occurred and the processes .The aim of the study is a comparative analysis and generalization of the state of development of digital transformation in the whole world, identifying problems and ways to overcome them. Particular attention is paid to the current state and prospects for the development of innovative technologies in thebanking sector of the economy in Kazakhstan.The methodology of the study was based on the study of the works of foreign and domestic authorsusing the theoretical generalization, system and comparative analysis, the method of statistical dataprocessing.Ideally, a digital banking system combines the advantages of two components: a new customerlook and an efficient operating model – both included by digitizing basic technologies, processes andstructures. From the outside, customers benefit from fair prices with increased transparency and comparability.The findings of the study show how banks meet these needs with immediate, high-qualityinteraction, and transactions are performed quickly and reliably. Customers are actively informed abouta large range of personalized products and services, including financial advice, new features and comparativeparameters.